Assessment of validated geoelectrical resistivity methods to reconstruct buried archaeological site (case study: Beteng Site-Sidomekar, Jember Regency). (February 2019) - Supriyadi,; Suprianto, Agus; Priyantari, Nurul; Eko Cahyono, Bowo; Sholeha, Imroatus
Abstract: Jember Regency has many relics of historical objects spread in some sub-districts, one of which is Beteng Site located in Sidomekar Village, Semboro Sub district - Jember. Beteng site is one of the relics of the Majapahit period, with an area of 93, 5 m x 40, 5 m. Inside of the site, there is red brick which is the vestige of the castle's foundation, a small part exposed on the surface and most still buried beneath the soil surface. The real condition of the Beteng Site with its limitations interesting to further investigated about its relevance to the history of the Majapahit Kingdom and the reconstruction of the fortress design and its function based on the mapping of the foundation of the building. The result of laboratory measurement of exposed red brick resistivity value is 17, 5 Ωm. The used values as a reference for analysing the field measurement results with 2D geo-electrical resistivity methods using Wenner-Schlumberger configuration. The measurement result using the geo-electrical resistivity method shows that the resistivity value of 22.1 Ωm - 25, 0 Ωhm in every line with depth 1 m - 2 m. This is quite close to the results of laboratory measurements, so it is presumed to be a red brick layer. Based on the distribution result of resistivity value in every line and real condition in the form of an exposed red brick, distribution of artifacts can be mapped to estimate the design of the foundation building of the castle's vestige.